1995
DOI: 10.1021/jm00018a022
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomimetic inhibitors of herpes simplex virus ribonucleotide reductase: a new class of antiviral agents

Abstract: We have been investigating a new class of antiviral compounds effective against herpes simplex virus (HSV) in vitro and in vivo. Antiviral activity results from inhibition of HSV ribonucleotide reductase (RR). The inhibitors are designed as mimics of the RR small subunit C-terminus, a region essential for RR subunit association and consequently enzymatic activity. Inhibition results from specific binding of the inhibitor to the HSV RR large subunit thereby preventing subunit association. This report details th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 6 publications
0
40
0
Order By: Relevance
“…In vitro studies have shown that inhibitors of cellular RR or the HSV-1 or VZV RRs (including HU, FMdC, A723U, A1110U, BW348U87, and the “BILD” series of peptidomimetics) exhibit antiviral activity when used alone and either potentiate or result in synergy when used in combination with ACV against wild type or drug-resistant strains of VZV, HSV-1, or HSV-2 (Bridges et al, 1995; Duan et al, 1998; Ellis et al, 1989; Lawetz and Liuzzi, 1998; Liuzzi et al, 1994; Moss et al, 1996, 1995; Neyts and De Clercq, 1999; Prichard and Shipman, 1995; Sergerie and Boivin, 2008; Spector et al, 1985, 1987, 1989). HU has also been shown to potentiate the activity of cidofovir and to synergize with GCV to inhibit replication of wild type or drug-resistant strains of HSV-1 or HSV-2 (Neyts and De Clercq, 1999; Sergerie and Boivin, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that inhibitors of cellular RR or the HSV-1 or VZV RRs (including HU, FMdC, A723U, A1110U, BW348U87, and the “BILD” series of peptidomimetics) exhibit antiviral activity when used alone and either potentiate or result in synergy when used in combination with ACV against wild type or drug-resistant strains of VZV, HSV-1, or HSV-2 (Bridges et al, 1995; Duan et al, 1998; Ellis et al, 1989; Lawetz and Liuzzi, 1998; Liuzzi et al, 1994; Moss et al, 1996, 1995; Neyts and De Clercq, 1999; Prichard and Shipman, 1995; Sergerie and Boivin, 2008; Spector et al, 1985, 1987, 1989). HU has also been shown to potentiate the activity of cidofovir and to synergize with GCV to inhibit replication of wild type or drug-resistant strains of HSV-1 or HSV-2 (Neyts and De Clercq, 1999; Sergerie and Boivin, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, C-terminal Rnr2-based peptidomimetics (14-16) bind Rnr1, blocking RNR assembly and providing another mode of therapy for proliferative diseases such as cancer. Early reports on Rnr2 peptide-based inhibitors showed that they had in vivo efficacy against herpes simplex virus with nM dissociation constants (17)(18)(19), suggesting that similar potencies might be possible with anticancer peptidomimetics.…”
mentioning
confidence: 99%
“…However, replacement of the acetyl group in compound 2 with a 3-phenylpropionyl group (compound 3) increased binding potency over 30 times. 11 Compound 3 provided the starting point for structure-activity studies that led to the discovery of ribonucleotide reductase inhibitors effective at preventing HSV replication in vitro and in vivo. 5 The binding potency increase associated with the 3-phenylpropionyl group (illustrated by compound 3) and related derivatives proved to be very important for inhibitor antiviral activity.…”
Section: Resultsmentioning
confidence: 99%
“…5000-fold. 11 As it was evident that a lipophilic group at this position was essential for good inhibitor potency, we speculated that the N-terminal NH in compound 4 might serve to more favorably position the lipophilic group for binding to R1. However, sequential truncation of the (ethylpropyl)amino group in 4 to a methyl group (compounds 5 and 6) culminated in a 2800-fold loss of potency.…”
Section: Resultsmentioning
confidence: 99%